Animal Guising and the Kentish Hooden Horse - Kargotis, Demetrios; Macdonald, Dash; Mortimer, Nicholas (My University, 2023)
Autohoodening was presented as part of the exhibition Animal Guising and the Kentish Hooden Horse at Maidstone Museum (2023), exploring the adaptation of historic animal guising traditions within contemporary socio-economic contexts. Through costume, props, and video documentation, Post Workers Theatre reinterpreted the Hooden Horse custom as a performative framework addressing precarious labour in the gig economy. The work demonstrates how folk traditions can be reactivated as critical design practices, bridging heritage, performance, and socially engaged research.